Multiple Sulfatase Deficiency (MSD): Review of the Literature and Case Reports of Two Siblings with Dental Caries and Trauma - Lorna Hirst; Gehan Abou-Ameira; Mari-Liis Uudelepp (Hindawi Limited, 2021)
Multiple sulfatase deficiency (MSD) (MIM # 272200) is an extraordinarily rare inborn error of metabolism (IEM). The phenotypic spectrum is largely heterogeneous and attributed to the combined effects of deficiencies in the nine sulfatases currently known to be related to human diseases. Systemic sequelae of MSD are vast and multisystemic, primarily encompassing developmental delay and neurological, cardiopulmonary, dermatological, gastroenterological, and skeletal manifestations. The dental phenotype is scarcely described in the literature due to a paucity of cases. Dental treatment under local and general anaesthesia mandates an integrated multidisciplinary approach to safeguard systemic health and optimise outcomes. This paper presents two siblings with multiple sulfatase deficiency who presented to the Paediatric Dental Department at Great Ormond Street Hospital, requiring comprehensive care under general anaesthesia for dental caries and trauma.